Determinants of Patient‐Reported Psoriatic Arthritis Impact of Disease: An Analysis of the Association With Sex in 458 Patients From Fourteen Countries. Issue 12 (27th November 2020) - Orbai, Ana‐Maria; Perin, Jamie; Gorlier, Clémence; Coates, Laura C.; Kiltz, Uta; Leung, Ying Ying; Palominos, Penelope E.; Cañete, Juan D.; Scrivo, Rossana; Balanescu, Andra; Dernis, Emmanuelle; Tälli, Sandra; et al.
Abstract : Objective: Sex differences may modify symptoms, disease expression, and treatment effects. The objective of this study was to evaluate the link between life impact and sex in psoriatic arthritis (PsA). Methods: Remission and Flare in Psoriatic Arthritis (ReFlaP; ClinicalTrials.gov identifier: NCT03119805) was a study in 14 countries of consecutive adult patients with definite PsA. Participants underwent comprehensive PsA assessment using the following measures: Disease Activity in Psoriatic Arthritis (DAPSA), Minimal Disease Activity (MDA), and Psoriatic Arthritis Impact of Disease (PsAID). Disease activity was compared by sex using t ‐tests or Wilcoxon tests. The association of PsAID with sex was analyzed using hierarchical generalized linear models. Results: Of 458 participants, 50.2% were male and the mean ± SD age was 53.1 ± 12.6 years. The mean ± SD PsA duration was 11 ± 8.2 years, and 51.5% of participants were being treated with biologic disease‐modifying antirheumatic drugs. Women, compared to men, had worse mean ± SD Leeds Enthesitis Index scores (0.8 ± 1.7 versus 0.3 ± 0.9), pain on a numerical rating scale (NRS; range 0–10) (4.7 ± 2.7 versus 3.5 ± 2.7), HAQ DI scores (0.9 ± 0.7 versus 0.5 ± 0.6), fatigue on an NRS (5.2 ± 3 versus 3.3 ± 2.8), and PsAID scores (4.1 ± 2.4 versus 2.8 ± 2.3) ( P < 0.001 for all). Women were also less frequently at treatment target compared to men according to DAPSA (cutoffs of ≤4 for remission and >4 and ≤14 for low disease activity; mean ± SD score 16.9 ± 14.9 in women versus 12.6 ± 16.6 in men) and MDA (25.7% versus 50.0%; P < 0.001 for all) scores. High life impact (PsAID score ≥4) was associated with female sex (odds ratio [OR] 2.3), enthesitis (OR 1.34), tender joints (OR 1.10)( P < 0.001 for all), and comorbidities (OR 1.22, P = 0.002). Conclusion: High life impact was independently associated with female sex, enthesitis, comorbidities, and tender joints. At treatment target, women had higher life impact compared to men. It is necessary for life impact to become a part of PsA treat‐to‐target strategies.